Development of an Agricultural Soil Information System - Dorka, Dénes (Acta Agraria Debreceniensis, 2003)
Since the development of remote sensing nearly 60 years ago, there have been many applications for agriculture. Some have proved effective, while others have not succeeded in assisting farmers with problem solving. Recent advances in the spatial, spectral and temporal resolution of remote sensing as well as potential positive changes in cost and availability of remotely sensed data may make it a profitable tool for more farmers. The target area of my research program is the fields cultivated by Kasz-Coop Ltd. considering that this firm is one of the main agricultural firms in the region and its cultivated fields are quite heterogeneous.